The Communist and the Communist's Daughter : A Memoir - Lazarre, Jane (Book collections on Project MUSE., 2017)
In this poignant memoir Jane Lazarre tells the fascinating history of her father Bill, a radical activist who, as part of his tireless efforts to create a better world for his family, held leadership positions in the American Communist Party, fought in the Spanish Civil War, and organized labor unions.